PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK TANI (POKTAN) TANAMAN ANGGREK PARAKAN JAYA KOTA TANGERANG SELATAN - Romadhon, Sahri; Muhtadi, Muhtadi (JURNAL AGRIBISNIS TERPADU, 2018)
This research invites readers to explore how the program works in Kelompok Tani Parakan Jaya. Here, the researcher shows several steps of observation: 1. Empowerment stages; 2. Enabling and inhibiting factors; 3. Economic and social impacts toward Kelompok Tani Parakan Jaya. However, this research is descriptive qualitative research method in which the research proposed to describe a uniqe community. There are some steps in collecting data: 1. Interview; 2. Observation; 3. Informan selection; 4. Data analysis. The result of this research shows that the implementation of various empowerment stages in Kelompok Tani Parakan Jaya has been well implemented, although there are several stages that have not been fully implemented, specifically on the stages of evaluation and termination. Secondly, people who has been participating in the program gain positive impact in economic and social sector directly. Economically, the members of the group earn an increased income if calculated monthly or based on income at eachharvest period. Besides, socially, this program creates good value and norms (good relationship) among the communites, especially for the participants. Lastly, in enabling and inhabiting factors found that the commmunity in Jalan Arjuna Parakan has succeded in utilizing the resources well as a source of livelihoodin which thiscontinual process motivates the community to reach progressive life.